The Effect of Using Internet on the Achievement of the M.A. Students in Educational Planning in Al-al Bayt University - Shedifat, Yahya (Jordan Journal of Educational Sciences, 2007)
This study aimed at investigating the effect of using the Internet on the achievement of the M.A. students in educational planning in Al- al Bayt University. The sample of the study consisted of all the students in the educational planning course in Al-al Bayt University in the academic year 2005 / 2006. consisted of (59) students. The control group consisted of (15) male and (14) female students who were taught by using traditional method while the experimental group consisted of (18) male and (12) female students who were taught by using the Internet. The researcher used amultiple choice achievement test. Its content validity was checked by experts in education. Its reliability was checked by using KR-20.The results showed that there were statistically significant differences attributed to the effect of the teaching method in favor of the experimental group.The results also showed that there were no statistically significant differences attributed to gender. And there were no statistically significant differences attributed to the interaction between gender and teaching method. A number of recommendations were presented on the basis of the findings of the study.